В любви каждый за себя: повесть / М. С. Серова - Серова Марина Сергеевна (Бестселлер от Марины Серовой, 2008)
Экземпляры: К. Х. (20210702) / Инвентарный номер: 42041 / Цена: 54.90 / Авт.знак: С 32 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44